Research self-efficacy as Correlates of Research Competence of Library and Information Science Postgraduate Students’ in Selected Universities in South -West, Nigeria - Awodoyin, Anuoluwa F.; Olutoki, Adeola E.; Osoba, Monisola Adebanke (Communicate: Journal of Library and Information Science, 2024)
Postgraduate education is fundamentally research-intensive, demanding a high level of research self-efficacy and research competence which are crucial for academic success and professional development. Therefore, this study investigated research self-efficacy as predictor of research competence of Library and Information Science (LIS) postgraduate students. Descriptive survey research design of the correlational type and total enumeration method was adopted. A self -developed questionnaire was administered to two hundred and eighty seven (287) postgraduate students. However, a total of 203(70.73%) copies of questionnaires were returned and found useful for the study. The findings of the study revealed that the level of research self-efficacy of the LIS PG students was fair. It was also revealed that the level of research competence of the LIS PG students’ was high. The study found out that there was significant difference in the research competence of the LIS postgraduate students’ (P= 0.039<0.05) based on gender. The study therefore concludes that research self-efficacy, and research competences are key tools that promote research success among postgraduate students. The study recommends among other things that universities should foster an inclusive and supportive research environment that values diverse perspectives and experiences which will contribute to closing the gender gap in the research competence of LIS PG students.